‘El canto y lira mía’: The Horatian authorial persona in the work of Fray Luis de León - Czepiel, M (Liverpool University Press, 2022)
In this study I discuss the generic implications of Fray Luis’s adoption of the Horatian authorial persona. Firstly, I interpret Ode I as a statement of his poetic programme. Next, I argue that in Ode XXII Fray Luis navigates lyric’s apparent rejection of epic themes by modelling his portrayal of Pedro Portocarrero on Horace’s relationship with Maecenas. I then discuss how other elevated poems are compatible with the lyric persona through their affiliation with the hymn form and particularly with Pindar’s lyric. Critics often comment that Fray Luis avoids amatory themes; while this is true in his original poetry, I argue that in his translations of Horace and in his use of Classical allusion in the Latin commentary In Canticum Canticorum, the lyric persona gives him both the licence to treat amatory themes and the ability to distance himself from them through Horatian humour. En este artículo, analizo el uso que hace Fray Luis de la figura del poeta lírico horaciano. En primer lugar, propongo que en la oda I el poeta desarrolla su programa poético. Al analizar el supuesto rechazo de la materia épica por parte de los poetas líricos antiguos, interpreto la representación de Pedro Portocarrero en la oda XXII a la luz de la relación entre Horacio y Mecenas. Otros poemas de tono elevado son compatibles con el género lírico debido a su relación con el himno lírico, y en particular con la poesía de Píndaro. Muchos estudiosos consideran que Fray Luis evita los temas amatorios; aunque esto es cierto por lo que respecta su poesía original, demuestro que en sus traducciones de Horacio y en sus alusiones a textos clásicos en el comentario In Canticum Canticorum, la figura del poeta lírico le permite tratar temas amatorios y simultáneamente distanciarse de ellos.